Integrasi Sejarah Lokal Tower Air Belanda dalam Pembelajaran Sejarah - munira, widia (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
History is understanding and learning that can create those who understand history, face the past and see a better future. Therefore, the use of local historical heritage can convey historical value as part of inculcating student character. This study aims to introduce the historical learning of the historical heritage of Pidie Regency. The method used in this research is descriptive and qualitative through direct visits to the location, which is done by obtaining historical objects at the location of the "Dutch Air Tower". The results show that the historical site of the Dutch water tower in Pidie Regency can be used as a source of information on the history of Indonesia during the Indonesian colonial period. The existence of local history in history learning aims to maintain collective memory from generation to generation. They know local history, and the existence of this local historical site has academic records that can be used for students to reach and explore, especially the surrounding environment.